Flavored Versus Nonflavored Waterpipe Tobacco: A Comparison of Toxicant Exposure, Puff Topography, Subjective Experiences, and Harm Perceptions. Issue 9 (4th July 2018) - Ben Taleb, Ziyad; Breland, Alison; Bahelah, Raed; Kalan, Mohammad Ebrahimi; Vargas-Rivera, Mayra; Jaber, Rana; Eissenberg, Thomas; Maziak, Wasim
Abstract: Introduction: Flavored waterpipe (WP) tobacco is the main type of tobacco used by young WP smokers, and a major factor attracting youth to smoke. However, evidence regarding the effect of limiting flavor on WP smokers' experience continues to be lacking. This study aims at evaluating the effect of flavor restriction on WP smokers' toxicant exposure, smoking topography, subjective experiences and harm perception. Methods: Thirty-two WP smokers completed two, 45-minute ad libitum smoking sessions (preferred flavor vs non-flavored tobacco) in a crossover design pilot study. Plasma nicotine concentration and exhaled carbon monoxide (eCO) were measured before and after each smoking session. Puff topography was recorded throughout the smoking session. Participants completed survey questionnaires assessing subjective smoking experiences and harm perception. Results: Significant differences were observed in plasma nicotine concentration between the two WP tobacco conditions, with a higher increase in plasma nicotine concentration following the flavored tobacco session. There were no significant differences between the two WP tobacco conditions for eCO and smoking topography measures. Compared with the non-flavored WP tobacco, we documented enhanced subjective smoking measures of satisfaction, calmness, taste, puff liking and enjoyment following the preferred flavored WP tobacco session. Cigarette harm perception was significantly higher among participants after smoking their preferred flavor compared with non-flavored WP tobacco. Conclusions: Limiting tobacco flavor has a substantial effect on WP smokers' nicotine exposure, subjective experience and harm perception. Therefore, eliminating or restricting WP flavors could be an essential element of comprehensive tobacco control policies to reduce the appeal of WP tobacco products for youth. Implications: This study highlights the important role of flavor in shaping WP smokers' experiences and exposures and the potential impact that regulating flavored WP tobacco may have on curbing WP use among youth in the US. Such regulations may reduce the appeal and the interest in WP smoking initiation and continued use.